FROM SECURITY TO SAFETY HERO: EDUKASI DAN PELATIHAN PERTOLONGAN PERTAMA - Simarmata, Jon Parulian; Pangkey, Ballsy C. A.; Tompunu, Marianna Rebecca Gadis; Pangemanan, Alice Yvonne Yovita; Sihombing, Yulia (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Background: First aid is the initial action taken before someone is taken to hospital when they experience health problems such as accidents, fainting, insect bites, broken bones, bleeding, or other conditions. Accidents and health problems can occur anywhere, whether at home or at work. A security officer may face injuries, broken bones, fainting, and situations that will cause problems for themselves or others. Therefore, proper first aid measures are very important. First aid is so important that basic first aid training must also be known by security officers. Objective: This Community Service programme focuses on providing education and training on first aid to security personnel to improve the safety of themselves, visitors, and other employees. Method: The community service activity uses a method of outreach, discussion, and training. The outreach and training are presented by the community service team from the Faculty of Nursing, Pelita Harapan University. This activity was attended by 100 security personnel from PT BSS Jakarta and evaluated using a pre-post test. Results: The community service activity was carried out successfully with a pre-test score of 66.02 and a post-test score of 83.47. The activity showed an increase in knowledge after education and training were provided. It is hoped that the community service first aid activity can be carried out on an ongoing basis.